In situ NMR investigation of the native chemical ligation (NCL) of N-terminal cysteines to alginate - David Bučak Gasser; Tobias Steindorfer; Dmytro Neshchadin; Georg Gescheidt; Karin Stana Kleinschek; Rupert Kargl (Carbohydrate Polymers, 2026)

Adaptive Modeling to Inform Environmental Management - Katie Irving; Rupert Mathwin; Christopher J. Kotalik; J. Angus Webb; David M. Walters; Siwan Lovett; S. Kyle McKay; Christa L. Torrens; John R. Olson; Ziad A. El Jack (Environmental Management, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Ion-driven communication and acclimation strategies in microalgae - Raquel Amaral; Damiano Duci; Francisco C. Cotta; Felipe L. Bacellar; Soraia Oliveira; Frédéric Verret; Kamal Asadi; Lode K.J. Vandamme; Nuno M. Reis; Lee D. Bryant; David Tosh; Jean-Luc Mouget; et al. (Chemical Engineering Journal, 2023)

Transfer of polychlorinated, polybrominated and mixed-halogenated dioxins, furans and biphenyls, polychlorinated naphthalenes and alkanes, polycyclic aromatic hydrocarbons and chlorobenzenes to the milk of dairy cattle from controlled ingestion of industrial and municipal bioresources recycled to agricultural land - Hannah Rigby; Alan Dowding; Alwyn Fernandes; David Humphries; Rupert G. Petch; Christopher K. Reynolds; Martin Rose; Stephen R. Smith (Science of The Total Environment, 2023)

Meta‐Fish‐Lib : A generalised, dynamic DNA reference library pipeline for metabarcoding of fishes - Rupert A. Collins; Giulia Trauzzi; Katherine M. Maltby; Thomas I. Gibson; Frances C. Ratcliffe; Jane Hallam; Sophie Rainbird; James Maclaine; Peter A. Henderson; David W. Sims; Stefano Mariani; Martin J. Genner (Journal of Fish Biology, 2021)
The accuracy and reliability of DNA metabarcoding analyses depend on the breadth and quality of the reference libraries that underpin them. However, there are limited options available to obtain and curate the huge volumes of sequence data that are available on public repositories such as NCBI and BOLD. Here, we provide a pipeline to download, clean and annotate mitochondrial DNA sequence data for a given list of fish species. Features of this pipeline include (a) support for multiple metabarcode markers; (b) searches on species synonyms and taxonomic name validation; (c) phylogeny assisted quality control for identification and removal of misannotated sequences; (d) automatically generated coverage reports for each new GenBank release update; and (e) citable, versioned DOIs. As an example we provide a ready‐to‐use curated reference library for the marine and freshwater fishes of the U.K. To augment this reference library for environmental DNA metabarcoding specifically, we generated 241 new MiFish‐12S sequences for 88 U.K. marine species, and make available new primer sets useful for sequencing these. This brings the coverage of common U.K. species for the MiFish‐12S fragment to 93%, opening new avenues for scaling up fish metabarcoding across wide spatial gradients. The Meta‐Fish‐Lib reference library and pipeline is hosted at https://github.com/genner-lab/meta-fish-lib .

A Quantitative Meta-analysis of Olfactory Dysfunction in Epilepsy - Kiran Khurshid; Andrew J. D. Crow; Petra E. Rupert; Nancy L. Minniti; Melissa A. Carswell; Dawn J. Mechanic-Hamilton; Vidyulata Kamath; Richard L. Doty; Paul J. Moberg; David R. Roalf (Neuropsychology Review, 2019)

Spatio‐temporal patterns of tree growth as related to carbon isotope fractionation in European forests under changing climate - Tatiana A. Shestakova; Jordi Voltas; Matthias Saurer; Frank Berninger; Jan Esper; Laia Andreu‐Hayles; Valérie Daux; Gerhard Helle; Markus Leuenberger; Neil J. Loader; Valérie Masson‐Delmotte; Antonio Saracino; et al. (Global Ecology and Biogeography, 2019)
Aim The aim was to decipher Europe‐wide spatio‐temporal patterns of forest growth dynamics and their associations with carbon isotope fractionation processes inferred from tree rings as modulated by climate warming. Location Europe and North Africa (30‒70° N, 10° W‒35° E). Time period 1901‒2003. Major taxa studied Temperate and Euro‐Siberian trees. Methods We characterize changes in the relationship between tree growth and carbon isotope fractionation over the 20th century using a European network consisting of 20 site chronologies. Using indexed tree‐ring widths (TRW i ), we assess shifts in the temporal coherence of radial growth across sites (synchrony) for five forest ecosystems (Atlantic, boreal, cold continental, Mediterranean and temperate). We also examine whether TRW i shows variable coupling with leaf‐level gas exchange, inferred from indexed carbon isotope discrimination of tree‐ring cellulose (Δ 13 C i ). Results We find spatial autocorrelation for TRW i and Δ 13 C i extending over a maximum of 1,000 km among forest stands. However, growth synchrony is not uniform across Europe, but increases along a latitudinal gradient concurrent with decreasing temperature and evapotranspiration. Latitudinal relationships between TRW i and Δ 13 C i (changing from negative to positive southwards) point to drought impairing carbon uptake via stomatal regulation for water saving occurring at forests below 60° N in continental Europe. An increase in forest growth synchrony over the 20th century together with increasingly positive relationships between TRW i and Δ 13 C i indicate intensifying impacts of drought on tree performance. These effects are noticeable in drought‐prone biomes (Mediterranean, temperate and cold continental). Main conclusions At the turn of this century, convergence in growth synchrony across European forest ecosystems is coupled with coordinated warming‐induced effects of drought on leaf physiology and tree growth spreading northwards. Such a tendency towards exacerbated moisture‐sensitive growth and physiology could override positive effects of enhanced leaf intercellular CO 2 concentrations, possibly resulting in Europe‐wide declines of forest carbon gain in the coming decades.

Imaging of changes in copper trafficking and redistribution in a mouse model of Niemann-Pick C disease using positron emission tomography - Julia Baguña Torres; Zilin Yu; Jayanta Bordoloi; Kavitha Sunassee; David Smith; Claire Smith; Oscar Chen; Rupert Purchase; Karin Tuschl; John Spencer; Frances Platt; Philip J. Blower (BioMetals, 2019)

Chromosome 18 gene dosage map 2.0 - Jannine D. Cody; Patricia Heard; David Rupert; Minire Hasi-Zogaj; Annice Hill; Courtney Sebold; Daniel E. Hale (Human Genetics, 2018)

Evolving Information Priorities of Hematologic Cancer Survivors, Caregivers, and Other Relatives - Ted Gansler; James Kepner; Erika Willacy; Cindy Soloe; Douglas Rupert; Meredith Jarblum; David Driscoll; Alex Orr; Tania Fitzgerald; Angelina Esparza (Journal of Cancer Education, 2010)

Sediment phosphorus cycling in a large shallow lake: spatio-temporal variation in phosphorus pools and release - Bryan M. Spears; Laurence Carvalho; Rupert Perkins; Alex Kirika; David M. Paterson (Hydrobiologia, 2007)

Chemokine expression is associated with the accumulation of tumour associated macrophages (TAMs) and progression in human colorectal cancer - Charles Bailey; Rupert Negus; Alistair Morris; Paul Ziprin; Robert Goldin; Paola Allavena; David Peck; Ara Darzi (Clinical & Experimental Metastasis, 2007)